Spectrophotometric data
Table of spectrophotometer and pH readings of various substances, including strychnine, caffeine, amphetamine, benadryl, and ascorbic acid. As this document is undated and vaguely titled, it is unclear which instrument was used to obtain these readings, although it was stored with others relating to the Beckman DU Spectrophotometer. The first Beckman Instruments DU Spectrophotometer was developed in 1940, when the company was still called National Technical Laboratories. Spurred by employee Howard Cary (who had previously been involved in pH meter development), NTL produced its first DU Spectrophotometer in 1940. This first Model A contained a glass prism, while subsequent models used quartz crystal. The DU was initially developed under a U.S. government contract, but was ultimately used in many important scientific discoveries and developments of the 20th century, including penicillin and synthetic rubber research, petroleum refining, and the creation of explosives.
Keywords: Ultraviolet spectroscopy; Scientific apparatus and instruments; Spectrophotometer; Beckman Instruments, Inc.